Survey on hepatic sarcoidosis in Italy. (March 2023) - Corte, C. Della; Reati, R.; Malinverno, F.; Arena, I.; Campigotto, M.; Cardinale, V.; Cespiati, A.; Degasperi, E.; Del Poggio, P.; Durante, E.; Federico, A.; Galati, G.; et al.
Abstract : Introduction: Sarcoidosis is a granulomatous disease that can potentially involve all body tissues, including the liver in about 10-20% of cases (1-4). High quality data on the management of hepatic sarcoidosis (HS) are scarce. In absence of national and international guidelines, management of HS is still experienced-based. Aim: This survey was carried out amongst Italian hepatologists to describe their practices in the management of patients with HS. Methods, Results: 1985 questionnaires were forwarded, of which 37 were completed and returned. Thirty-three centers reported managing patients with HS, 17 (51%) of these reported managing more than one patient. Twenty-seven (81%) centers obtained the diagnosis by liver biopsy, the remaining centers by radiological techniques or biopsy in other sites. In coexistence with HS, the pulmonary sarcoidosis was reported from 18 (54%) centers, while patients with no other localization, except for the hepatic one, were followed up in 6 (18%) centers. Twenty-two (66%) centers treated such patients with first-line steroid therapy, the remainders reported using other drugs. Finally, 3 (9%) centers reported the presence of transplant patients, other 3 (9%) centers of deceased patients. Conclusion: HS is a rare entity in Italy and there is a wide variation in diagnostics and therapeutics. A multicentric, prospective, national cohort study is needed to study this disease.